Occupational stress and job satisfaction among beginner teachers in secondary schools in Kuching-Samarahan division, Sarawak - Choo, Thiam Choy (Faculty of Computer Science and Information Technology, 2000)
The purpose of this study was to investigate the level of occupational stress and job satisfaction among beginner teachers in the Kuching-Samarahan Division, Sarawak. Factors causing the occupational stress and job satisfaction were also identified and ranked. In addition, a correlation between job satisfaction and occupational stress among beginner were conducted.